Efektivitas Pembelajaran Kitab At-Tibyan dalam Meningkatkan Adab Membaca Al-Qur’an pada Santri Pondok Pesantren Baiturrahmat - Maimon, Maimon; Rosidi, Ayep; Hadi, Imam Anas (Universitas Muhammadiyah Magelang, 2026)
This study aims to test the effectiveness of learning the At-Tibyān book in improving the etiquette of reading the Qur'an in students at the Baiturrahmat Islamic Boarding School. The study used a quantitative approach with a pre-experimental one-group pretest-posttest design involving 30 students. The results showed that the average score of the etiquette of reading the Qur'an increased from 51.37 in the pretest to 77.97 in the posttest. The results of the paired sample t-test showed a significant difference between the pretest and posttest scores with a Sig. (2-tailed) < 0.001, while the N-Gain analysis showed an average value of 0.5321, which is included in the moderate category. These findings indicate that learning the At-Tibyān book is effective in improving the etiquette of reading the Qur'an in students.